Financial Inclusion and Economic Growth: The Role of Islamic Microfinance - Wildan, Wildan Nasri; Alfarizi, Muhammad Alfarizi; Isnaini, Muhammad Isnaini (Cattleya Darmaya Fortuna, 2023)
Financial inclusion is one of the important elements in driving economic growth, especially in developing countries. In Indonesia, the role of Islamic microfinance is increasingly important in increasing public access to fair and sharia-based financial services. This study aims to analyze the contribution of Islamic microfinance to financial inclusion and its impact on economic growth. In this study, the author explores various models of Islamic microfinance, such as mudharabah, musyarakah, and murabahah-based financing, which can provide access to people who are not covered by the conventional banking system. Using qualitative and quantitative approaches, this study finds that Islamic microfinance not only increases financial inclusion but also has a positive impact on poverty alleviation and community economic empowerment. This study concludes that strengthening the Islamic microfinance sector can be an effective strategy in creating inclusive and sustainable economic growth in Indonesia.